Ultrasonographic adrenal gland changes in dogs with Cushing’s syndrome with a low-dose dexamethasone suppression test result consistent with partial suppression or escape pattern - Mayr, Matthias; Geisen, Vera; Unterer, Stefan; Wehner, Astrid (Frontiers in Veterinary Science, 2024)
BackgroundCushing’s syndrome (CS) in dogs is mainly caused by pituitary-dependent (PDH) or adrenal-dependent (ADH) hypercortisolism. Result of the low-dose-dexamethasone suppression test (LDDST) with partial suppression (PSP) or escape pattern (EP) are indicative of PDH. No data concerning the ultrasonographic characteristics of the adrenal glands from dogs with these patterns exists.ObjectiveTo describe ultrasonographic appearance of adrenal glands in dogs with CS, with a LDDS test result consistent with PSP or EP.AnimalsForty-nine client owned dogs with a diagnosis CS with a PSP or EP in the LDDST.MethodsRetrospective evaluation of ultrasonographic adrenal gland size, shape and echogenicity. The dorsoventral thickness ratio (DVTR) and dorsoventral thickness difference ratio (DVTDR) was calculated.ResultsPSP and EP occurred in 42.9 and 57.1% of all LDDST. The median maximum width of the left adrenal gland was 0.71 cm (IQR, 0.24 cm) and of the right 0.75 cm (IQR, 0.19 cm) in all dogs and there was no difference between both patterns. There was a significant correlation between adrenal gland width and weight (left adrenal gland p = 0.002, right adrenal gland p = 0.017). In 9/49 dogs (18.4%), an adrenal asymmetry with a DVTDR >0.3 was present. In 7 of these 9 dogs, follow-up was available indicating presence of PDH.Conclusions and clinical importanceBased on follow up, PSP and EP of the LDDST were very supportive of PDH. Bilaterally symmetric adrenomegaly is a characteristic finding in dogs with PDH, however the size of adrenal gland width in this cohort was smaller than previously reported. Adrenal asymmetry was noted in approximately 20%.